STUDY OF HOMEOSTASIS MODEL ASSESSMENT OF INSULIN RESISTANCE, DYSLIPIDEMIA, ANTIOXIDANT VITAMINS STATUS, SERUM CALCIUM, PHOSPHATE AND PROSTATE SPECIFIC ANTIGEN IN PROSTATE CANCER. - M.KRISHNAMMA; S.PRASANTH VARDHAN; J.N.NAIDU; M.PRASAD NAIDU (International Journal of Pharma and Bio Sciences, 2015)
The Incidence of Prostate Cancer is increasing day by day all over the world. At present the Incidence is about 5 per 1, 00,000 in India. There is strong evidence that genetic and environmental factors play in important role in pathophyology, of prostatic cancer. In this study HOMA-IR, serum Calcium, Phosphate, Lipid profile, PSA and antioxidant vitamins were estimated. Age matched 50 Prostate cancer cases and 50 controls included in the study. The insulin resistance in all cases and control groups evaluated by estimating fasting blood glucose and insulin levels, by using HOMA IR Formula. Antioxidant vitamins estimated by HPLC, Serum Calcium, Phosphate, lipid profile and Prostate specific antigen by enzymatic kits using Autoanlyzers. In the present study, the values of HOMA-IR, serum Calcium and PSA are (p<0.05) significantly increased than in controls. The Serum alfa tocopherol and ascorbic acid values in cases significantly reduced (p<0.05) than in controls. The growing of prostate cancer is a multifactorial. Insulin resistance, antioxidant vitamins status, hyper calcimeia and dyslipidemia play an important role in pathogenesis of prostate cancer.